Isolasi dan Karakterisasi Mikroorganisme Endofit Akar Ginseng Jawa (Talinum paniculatum Gaertn.) Yang Diberi Perlakuan Perbedaan Ketersedian Air - Visi Tinta Manik; Intan Nurcahya; Suhardjadinata; Susi Setiaramdani (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
A medicinal plant known as Java ginseng (Talinum paniculatum Gaertn.) may thrive in a variety of water availability situations. The quantity of endophytic bacteria a plant contains affects its capacity to survive in stressful environments. The objective of this study was to identify and separate endophytic bacteria from Javanese ginseng roots that had undergone various water availability treatments. A description method was utilized, in which isolated isolates were given morphological descriptions, assessed for similarity indexes, and then categorized. Endophytic microbe abundance and diversity varied according to this study, but plants treated with water scarcity displayed higher abundance and diversity. While endophytes of plant origin treated with 60% field capacity (FC) had the maximum diversity, root samples treated with 80% (FC) had the highest microbial abundance. Ten species groupings were created from the 42 isolated isolates based on a coefficient value of > 70%.